Potential of different strategies to increase intramuscular fat deposition in sheep: A meta-analysis study - Santos Torres, Rodrigo de Nazaré [UNESP]; Ghedini, Caren Paludo; Chardulo, Luis Artur Loyola [UNESP]; Baldassini, Welder Angelo [UNESP]; Curi, Rogério Abdallah [UNESP]; Pereira, Guilherme Luis [UNESP]; Schoonmaker, Jon Patrick; Almeida, Marco Tulio Costa; Costa, Ciniro [UNESP]; Neto, Otavio Rodrigues Machado [UNESP] (Elsevier, 2024)
We evaluated the potential of different strategies to increase intramuscular fat (IMF) deposition in sheep meat through meta-analytical methods. Additionally, this study aimed to investigate the interrelationship among diet composition, performance, carcass traits, meat quality, marbling score and IMF in sheep. The dataset was composed by 102 peer-reviewed publications. The strategies to increase IMF deposition in sheep meat were evaluated by examining the weighted mean difference (WMD) between control treatment and increased-IMF treatment (beta-agonist; glycerin; essential oil; vitamin E; lipids; tannins; feeding system and sex class). The interplay between factors such as dietary composition, performance, carcass and meat quality traits highlights how the intensification of production systems, characterized by a high grain content in the diet and shorter finishing periods, reduces IMF content of meat. The IMF content was greater in females (WMD = 0.52%; P<.0001) and castrated males (WMD = 0.53%; P = 0.001) compared to intact males. Lambs finished in feedlots exhibited a 19.23% higher IMF content (WMD = 0.74%; P <.0001) compared to those finished in pasture systems. The inclusion of lipids sources to the diets increased in IMF content (WMD = 0.11%; P = 0.008), while tannins sources decrease in IMF (WMD = −0.07%; P = 0.029). Marbling score did not prove to be an adequate indicator of IMF deposition in sheep meat, potentially due to biases in subjective marbling assessments. In conclusion, our findings suggest that the most effective strategy for enhancing IMF in lambs involves utilizing female or castrated males rather than intact males followed by finishing lambs on high concentrate diets in a feedlot. Genetics did not impact IMF in the evaluated studies while other dietary strategies to alter IMF deposition had mixed effects on IMF deposition. Tannin marginally decreased IMF, vitamin E had no effect, and lipid supplementation had varied effects on IMF deposition depending on the lipid source.
Keywords: Lamb; Marbling; Meat quality; PCA